Activation tagging identifies Arabidopsis transcription factor AtMYB68 for heat and drought tolerance at yield determining reproductive stages. (15th November 2020) - Deng, Mingde; Wang, Yang; Kuzma, Monika; Chalifoux, Maryse; Tremblay, Linda; Yang, Shujun; Ying, Jifeng; Sample, Angela; Wang, Hung‐Mei; Griffiths, Rebecca; Uchacz, Tina; Tang, Xurong; et al.
SUMMARY: Heat stress occurring at reproductive stages can result in significant and permanent damage to crop yields. However, previous genetic studies in understanding heat stress response and signaling were performed mostly on seedling and plants at early vegetative stages. Here we identify, using a developmentally defined, gain‐of‐function genetic screen with approximately 18 000 Arabidopsis thaliana activation‐tagged lines, a mutant that maintained productive seed set post‐severe heat stress during flowering. Genome walking indicated this phenotype was caused by the insertion of 35S enhancers adjacent to a nuclear localized transcription factor AtMYB68. Subsequent overexpression analysis confirmed that AtMYB68 was responsible for the reproductive heat tolerance of the mutant. Furthermore, these transgenic Arabidopsis plants exhibited enhanced abscisic acid sensitivity at and post‐germination, reduced transpirational water loss during a drought treatment, and enhanced seed yield under combined heat and drought stress during flowering. Ectopic expression of AtMYB68 in Brassica napus driven either by 35S or by heat‐inducible promoter recapitulated the enhanced reproductive heat stress and drought tolerance phenotypes observed in the transgenic Arabidopsis. The improvement to heat stress is likely due to enhanced pollen viability observed in the transgenic plants. More importantly, the transgenic canola showed significant yield advantages over the non‐transgenic controls in multiple locations, multiple season field trials under various drought and heat stress conditions. Together these results suggest that AtMYB68 regulate plant stress tolerance at the most important yield determining stage of plant development, and is an effective target for crop yield protection under current global climate volatility. Significance Statement: There is a significant gap in our knowledge on how plants cope with heat and drought stresses at the reproductive stages, which is critical for seed yield. Using a developmentally defined, gain‐of‐function genetic screen in Arabidopsis, this study reveals a transcriptional factor for enhancing heat and drought tolerance at yield determining reproductive stages.